Depression and anxiety in expectant and new fathers: longitudinal findings in Australian men. (June 2015) - Leach, Liana S.; Mackinnon, Andrew; Poyser, Carmel; Fairweather-Schmidt, A. Kate
Abstract : Background: Despite growing interest in men's perinatal mental health, we still know little about whether becoming a new father is associated with increases in psychological distress. Aims: To use prospective longitudinal data to investigate whether becoming a first-time expectant (partner pregnant) and/or new father (child <1 year) is associated with increases in depression and anxiety. Method: Men were aged 20–24 years at baseline ( n = 1162). Levels of depression and anxiety were measured at four time points over 12 years. Over this time, 88 men were expectant fathers, 108 men were new fathers and 626 men remained non-fathers. Results: Longitudinal mixed models showed no significant increase in depression or anxiety as a function of expectant or new fatherhood, as compared with pre-fatherhood levels. Conclusions: Our findings suggest that, generally, expectant and new fathers are not at greater risk of depression or anxiety. Future epidemiological research should continue to identify men who are most (and least) at risk to focus resources and assistance most effectively.